Eurasianism, Identity, and Russian Policy: A Lacanian Interpretation of Contemporary Eurasianist Discoruse - Mirishli, Zahra (My University, 2026)
This thesis analyzes contemporary Neo-Eurasianism through the combined perspectives of constructivism, Ontological Security Theory, and Lacanian psychoanalysis in order to explain the persistence and symbolic appeal of Eurasianist discourse within post-Soviet Russia. Existing scholarship on Eurasianism has largely interpreted the phenomenon through geopolitical, strategic, or civilizational approaches, frequently emphasizing Russian resistance to Western hegemony, NATO expansion, and the transformation of the post Cold War international order. While such approaches explain important dimensions of Russian foreign policy behavior, they remain insufficient for understanding the symbolic and affective intensity that characterizes contemporary Eurasianist discourse. The thesis argues that Neo-Eurasianism operates not only as a geopolitical doctrine, but also as a symbolic response to the crisis of post-Soviet identity formation. Drawing on Lacanian concepts such as constitutive lack, fantasy, desire, and the constitutive Other, the study demonstrates that Eurasianist narratives of multipolarity, civilizational sovereignty, historical continuity, and anti-Western resistance function as fantasies through which Russian political identity attempts to overcome experiences of fragmentation, uncertainty, and symbolic dislocation following the collapse of the Soviet Union. Methodologically, the thesis employs qualitative discourse analysis combined with theoretical and interpretive analysis of Eurasianist political narratives and intellectual texts. The research shows that geopolitical concepts within Neo-Eurasianism frequently acquire symbolic and existential significance extending beyond conventional strategic reasoning. The thesis concludes that the enduring political force of Eurasianism derives from its capacity to organize collective desire around visions of restored historical coherence and civilizational wholeness despite the structural impossibility of complete identity stabilization.
Keywords: Neo-Eurasianism; Lacanian Psychoanalysis; Russian Identity; Ontological Security; Political Fantasy; Russian Foreign Policy